Study on diesel engine characteristics using multi-walled carbon nanotubes blended thermal cracked vegetable oil refining waste. (2021) - Manieniyan, V.; Senthilkumar, R.; Sukumar, V.
Abstract: While fossil fuels are rapidly exhausted and emissions laws are becoming more stringent, alternatives to fossil fuels must be pursued urgently. Vegetable oil is the substitute diesel fuel most suitable. The current work focuses on to analyze the impact of multi-walled carbon nanotubes (MWCNT) blend in various proportion with 20 percentage of biodiesel from vegetable oil refinery by product such as thermal cracked Sunflower Acid towards the characteristics of a diesel engine. From this investigation the result shows the Specific fuel consumption significantly reduced while using in MWCNT40ppm B20TCGAO up to 5% compared and brake thermal efficiency was increased up to 4% compare to other blends of MWCNT. The emission HC, smoke density and CO were reduced except oxides of nitrogen. The best blend was selected as MWCNT40ppmB20TCGAO.